Kedai Kopi sebagai Ruang Ketiga di Dubai - Haliza, Shafira Nur; Suranta, Suranta (Middle Eastern Studies Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
This study explores coffee shops as third places within the socio-cultural life of Dubai’s urban society, as well as their influence on the development of the coffee industry. Despite not producing coffee beans locally, Dubai has become a center of innovation in the specialty coffee sector. This research employs a descriptive qualitative method, with data collected through literature review and social media observation of several coffee shops in Dubai. The theoretical framework includes the concepts of Third Place and Third Wave Coffee. The findings indicate that the implementation of third place concepts in Dubai’s coffee shops is dynamic, although aspects of social neutrality still present challenges, particularly with the visible expression of cultural identity among Emirati patrons. Nevertheless, modern coffee shops remain inclusive social spaces and extend their third place function into the virtual realm through social media. Government support has also driven the growth of the coffee industry, positioning Dubai as a hub for specialty coffee that blends global innovation with local identity, making coffee shops a symbol of social transformation that still values tradition.